2005
DOI: 10.1073/pnas.0408442102
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium liver stage developmental arrest by depletion of a protein at the parasite–host interface

Abstract: Plasmodium parasites of mammals, including the species that cause malaria in humans, infect the liver first and develop there into clinically silent liver stages. Liver stages grow and ultimately produce thousands of first-generation merozoites, which initiate the erythrocytic cycles causing malaria pathology. Here, we present a Plasmodium protein with a critical function for complete liver stage development. UIS4 (up-regulated in infective sporozoites gene 4) is expressed exclusively in infective sporozoites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
426
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 369 publications
(441 citation statements)
references
References 31 publications
9
426
2
4
Order By: Relevance
“…8,9 A central role of UIS3 in fatty acid uptake has been recently proposed. 10 Indeed, a yeast two-hybrid screen based on UIS3 of the rodent malaria parasite P. yoelii (Py-UIS3) identified mouse liver fatty acid binding protein (mL-FABP) as an interacting host protein.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 A central role of UIS3 in fatty acid uptake has been recently proposed. 10 Indeed, a yeast two-hybrid screen based on UIS3 of the rodent malaria parasite P. yoelii (Py-UIS3) identified mouse liver fatty acid binding protein (mL-FABP) as an interacting host protein.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, preerythrocytic stages of the rodent malaria parasites Plasmodium berghei and Plasmodium yoelii were attenuated by deletion of preerythrocytic-stage-expressed genes named Up-regulated in Infectious Sporozoites (UISs). UIS3 and UIS4 (7)(8)(9) are proteins of the liver-stage parasitophorous vacuole membrane, the principal host-parasite interface during liver infection (7,10). Deletion of UIS3 and UIS4 led to complete arrest of early liver-stage development after hepatocyte infection (7)(8)(9).…”
mentioning
confidence: 99%
“…UIS3 and UIS4 (7)(8)(9) are proteins of the liver-stage parasitophorous vacuole membrane, the principal host-parasite interface during liver infection (7,10). Deletion of UIS3 and UIS4 led to complete arrest of early liver-stage development after hepatocyte infection (7)(8)(9). Deletion of another UIS gene, P52, encoding a putative GPI-anchored protein (11,12), and P36, a gene encoding a putative secreted protein (12), also resulted in developmental arrest at the early stage of hepatocyte infection.…”
mentioning
confidence: 99%
“…Parasites that are underirradiated remain infectious, and those that are overirradiated do not induce protective immunity. Recently, it has been shown that genetically attenuated sporozoites (GAS) that lack sporozoitespecific conserved genes (uis3 and uis4) that are apparently important for sporozoite development in the hepatocyte can induce significant or complete protective immunity in the P. berghei rodent model of malaria when different immunization protocols are used (16,17). The use of GAS for vaccination might remove the uncertainty associated with RAS once a more thorough understanding of the mechanisms of immunity invoked by GAS and their developmental defect(s) are available.…”
mentioning
confidence: 99%